2024
DOI: 10.1186/s12933-023-02112-y
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control and cardiovascular outcomes in patients with diabetes and coronary artery disease according to triglyceride-glucose index: a large-scale cohort study

Zhangyu Lin,
Jining He,
Sheng Yuan
et al.

Abstract: Background The role of triglyceride-glucose (TyG) index, an insulin resistance indicator, in glycemic management for diabetic patients with coronary artery disease (CAD) was still unknown. Therefore, we aimed to explore the association between glycemic control and cardiovascular (CV) outcomes in patients with diabetes and CAD according to different TyG index levels. Methods A total of 9996 diabetic patients with angiograph-proven CAD were consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Helfand et al, demonstrated that patients with elevated glucose levels upon hospital admission had the highest in-hospital mortality rates (9.9%), surpassing the rates observed in individuals diagnosed with diabetes (6.5%) and those without diagnosed diabetes (7.5%) [ 44 ]. Similarly, Lin et al, in their study enrolling 9996 patients with diabetes and confirmed CAD revealed that glycaemic control, defined as HbA1c < 7%, was linked to a decreased risk of cardiovascular events, particularly in patients with a high triglyceride-glucose (TyG) index [ 45 ]. Another study, analysing data from six prospective, population-based cohort studies involving a total of 36,180 Europeans, found that HbA1c levels were independently associated with cardiovascular mortality, overall mortality, and cardiovascular morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Helfand et al, demonstrated that patients with elevated glucose levels upon hospital admission had the highest in-hospital mortality rates (9.9%), surpassing the rates observed in individuals diagnosed with diabetes (6.5%) and those without diagnosed diabetes (7.5%) [ 44 ]. Similarly, Lin et al, in their study enrolling 9996 patients with diabetes and confirmed CAD revealed that glycaemic control, defined as HbA1c < 7%, was linked to a decreased risk of cardiovascular events, particularly in patients with a high triglyceride-glucose (TyG) index [ 45 ]. Another study, analysing data from six prospective, population-based cohort studies involving a total of 36,180 Europeans, found that HbA1c levels were independently associated with cardiovascular mortality, overall mortality, and cardiovascular morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the impact of intensive glycemic control on cardiovascular outcomes remains uncertain, with specific studies suggesting a potential null or even adverse effect on these outcomes [ 4 ]. A large-scale cohort study revealed that maintaining controlled glycemia correlated with enhanced cardiovascular outcomes among diabetes patients with established CAD, particularly among those exhibiting elevated levels of the triglyceride-glucose (TyG) index, which is an indicator of insulin resistance [ 5 ]. The study noted that heightened TyG index levels associated heightened cardiovascular event risks.…”
Section: Reviewmentioning
confidence: 99%
“…The study noted that heightened TyG index levels associated heightened cardiovascular event risks. In contrast, controlled glycemia was linked to reduced cardiovascular event risks within the high TyG index subgroup, albeit not within the low and moderate TyG index subgroups [ 5 ]. Moreover, an additional study postulated that chronic hyperglycemia potentially contributes to coronary heart disease (CHD) in both diabetic and nondiabetic individuals, advocating for investigations into glucose-lowering strategies to mitigate heart disease risk [ 6 ].…”
Section: Reviewmentioning
confidence: 99%